2020
DOI: 10.1021/acs.jmedchem.0c01395
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing PEG-Extended Apelin Analogues as Cardioprotective Drug Leads: Importance of the KFRR Motif and Aromatic Head Group for Improved Physiological Activity

Abstract: Apelin is an important contributor to the renin-angiotensin axis, regulating cardiovascular, metabolic, and neurological functions. Apelin-17 has especially potent cardio-physiological effects but is rapidly degraded in human blood (t 0.5 ∼ 4 min). Angiotensin-converting enzyme 2 (ACE-2), neprilysin (NEP), and plasma kallikrein (KLKB1) cleave and inactivate it, with the latter cutting within the arginine−arginine site. Here, we show that analogues with an N-terminal polyethylene glycol (PEG) extension as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
(72 reference statements)
2
11
0
1
Order By: Relevance
“…A similar trend was found in human plasma (Table and Supporting Information, Figure S11). The different stability in human and mouse plasma may reflect the different proteases and/or activities, which is also seen in other reports . Consistently, in a pharmacokinetic analyses on E11 and Pal-E11, which were intravenously administered to mice at a 3 μmol/kg body weight (Supporting Information, Figure S12), Pal-E11 showed prolonged T 1/2 (22.58 ± 5.06 min) compared to that of E11 (0.35 ± 0.04 min).…”
Section: Results and Disscussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A similar trend was found in human plasma (Table and Supporting Information, Figure S11). The different stability in human and mouse plasma may reflect the different proteases and/or activities, which is also seen in other reports . Consistently, in a pharmacokinetic analyses on E11 and Pal-E11, which were intravenously administered to mice at a 3 μmol/kg body weight (Supporting Information, Figure S12), Pal-E11 showed prolonged T 1/2 (22.58 ± 5.06 min) compared to that of E11 (0.35 ± 0.04 min).…”
Section: Results and Disscussionsupporting
confidence: 82%
“…The different stability in human and mouse plasma may reflect the different proteases and/or activities, which is also seen in other reports. 50 Consistently, in a pharmacokinetic analyses on E11 and Pal-E11, which were intravenously administered to mice at a 3 μmol/kg body weight (Supporting Information, Figure S12), Pal-E11 showed prolonged T 1/2 (22.58 ± 5.06 min) compared to that of E11 (0.35 ± 0.04 min). Understanding the mechanism behind the high stability of Dimer-E11 in future studies may provide clues for the rationale design of elabela/apelin analogues.…”
Section: ■ Introductionsupporting
confidence: 57%
“…The therapeutic potential of APJ agonism by [Pyr 1 ]­apelin-13 is encouraging; however, low plasma stability makes it unsuitable for oral administration and chronic treatment . Synthetic modifications to the peptide have been made in an effort to increase plasma half-life including macrocyclization and backbone modifications, conjugation with polyethylene glycol or fatty acid scaffolds, as well as Fc-fusion constructs. An agonistic antibody for APJ has also recently been reported . During the course of our studies, additional small-molecule APJ receptor agonists have been reported in the literature, and subsequent to our work, the structure of the clinical lead AMG 986 (Figure ) was disclosed .…”
Section: Introductionmentioning
confidence: 81%
“…The short half-life of apelin in vivo has encouraged the development of metabolically stable apelin analogs for potential therapeutic applications. Numerous approaches ( Table 1 ), such as PEGylation ( 107 109 , 112 , 113 ), synthetic modifications to the RPRL motif of apelin ( 18 ), palmitoylation and the use of unnatural amino acids ( 38 , 103 , 107 , 114 , 115 ), or main-chain modifications (cyclization) ( 106 , 116 , 117 ), have now been used to increase the half-life of apelin peptides. Recent studies have reported the development of nonpeptidic ApelinR agonists that mimic the signaling properties of apelin, some of them are orally active ( Table 1 ) ( 104 , 110 , 111 ).…”
Section: The Apelin/avp Balance and Hyponatremiamentioning
confidence: 99%